Effects of Different Solvents to Printability in Gravure Printing - (:unkn) unknown (ASIAN JOURNAL OF CHEMISTRY, 2012)
There are different solvents used in Gravure printing inks. Also there are different properties of solvents which affect the printing quality in different ways. In this study, four different gravure inks with four different solvents has been prepared. Prepared ink has been printed with IGT FI Gravure and Flexo test machine on transparent low density polyethylene and opaque oriented polypropylene films. The used solvents amounts are not equal for same viscosity. This change also affects the printing quality. As a result, the fact that, which solvent constitutes the best print quality for gravure print on a low density polyethylene and oriented polypropylene has been understood.
Keywords: Gravure; Solvent; Gravure ink; Oriented polypropylene; Low density polyethylene; Print quality